Evidence of autopolyploidy and translocations in the karyotype of Tigridia pavonia (Iridaceae, Iridoideae) from the Reserva Ecológica del Pedregal de San Ángel, Mexico - Tapia-Pastrana, Fernando; Tapia-Aguirre, Fernando (Instituto de Ecología, A.C., 2017)
Background and Aims: Tigridia pavonia was proposed as an allotetraploid taxon 2n=4x=28, but without cytogenetic evidence supporting its hybrid origin. It is a widespread species in Mexico and its populations lack karyotype and detailed analysis of chromosomes with satellites as a criterion to determine the number of nucleolar organizers that confirm or not nucleolar dominance. In this paper, we analyze and describe the number and chromosome architecture of T. pavonia from a Mexican population in search of evidences that support or discard its hybrid origin and we propose a karyotype according to the level and origin of ploidy.Methods: A surface spreading and air drying technique was used that includes enzymatic maceration and hypotonic shock in meristem roots to obtain mitotic chromosomes from six individuals of T. pavonia native to the Reserva Ecológica del Pedregal de San Ángel, Mexico City.Key results: A bimodal karyotype with 28 chromosomes was confirmed, which according to their similar morphology were included in seven groups of four homologous chromosomes each. All chromosomes in the smallest group exhibited secondary constrictions associated to macrosatellites and this shows the absence of nucleolar dominance or differential amphiplasty. Moreover, in the group of largest chromosomes configurations were observed that suggest rearrangements by translocations. The haploid karyotype 6m + 8sm is proposed here.Conclusions: Cytogenetically, the presence of four satellites discards an allotetraploid origin and the evidence of possible translocations correlates with fragments, B chromosomes and fragile centromeres observed in other species of this genus. This supports the active role of translocations in the conformation of bimodal karyotype of T. pavonia.